Human sperm vitrification: A scientific report. (16th July 2020) - Schulz, Mabel; Risopatrón, Jennie; Uribe, Pamela; Isachenko, Evgenia; Isachenko, Vladimir; Sánchez, Raúl
Abstract: Background: The sperm vitrification developed by this group is based on the ultrarapid freezing of a vitrification solution composed of a non‐permeable cryoprotectant (saccharides and protein), in which previously selected spermatozoa are resuspended, free of seminal plasma, and then plunged directly into liquid nitrogen. Compared to traditional sperm freezing, vitrification does not cause chemical or physical damage to the intracellular structures and reduces the damage to the plasma membrane because no ice crystals form, thus preserving motility and DNA integrity. Objectives: This manuscript is a review of the vitrification methodology developed by the authors' research group, including studies showing the application in human reproduction therapy. Materials and methods: The authors perform a review of the work initiated more than a decade ago by this research group, on the implementation of sperm vitrification, a more effective technique for cryopreservation of human spermatozoa, discussing the results obtained by other authors and the projection of this technique. Results and discussion: The vitrification technique has been developed in selected spermatozoa free of seminal plasma supplemented with saccharides such as sucrose, trehalose, and dextran, together with albumin, providing a high motility rate and protective structures of the cytoskeleton. In patients, it can be used to preserve their fertility for oncological reasons, genetics, inflammatory diseases, or reproductive medicine techniques. The possibility that vitrified spermatozoa can be preserved at temperatures of −80°C can simplify sample storage, optimizing the space and time as well as operator safety. Conclusion: Vitrification techniques have demonstrated the preservation of selected spermatozoa without seminal plasma and with non‐permeable cryoprotectants and protein. Currently, it is one of the most effective ways to maintain sperm function and has been used in in vitro fertilization or intrauterine insemination in humans, achieving healthy live births.